What does it mean to learn? Asking questions, thinking, learning from the point of view of philosophy for children - Flores, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this work is to support the thesis that we learn by thinking and we think when we ask questions, as opposed to the neoliberal thesis of learning by doing. A concept of education based on complexity is implied from this argumentation. Philosophy for children was used as a work methodology. A hermeneutic exercise was carried out to interpret data and to analyze what children were discussing. Issues such as questioning skills, forms of relationships that show attitudes, knowing how to argue and how to present results were addressed. This text presents a session which allowed for a detailed presentation of the results of this exercise.